Duelo y su influencia en el rendimiento académico de un adolescente - Moyano Bajaña, Erwin Alexander (2020)
Mourning is a stage that every person goes through in the face of the loss of a loved one and today several families in Ecuador and the whole world have been affected by the loss of a relative as a result of the global COVID-19 pandemic. This case study deals with a 17-year-old young man who is going through a grieving process due to the loss of his father due to the coronavirus disease, the young man's life was affected in different areas such as: social relations, academic study between other areas. Through the different techniques applied, a F32.1 called a moderate depressive episode was concluded according to the CIE-10. The patient underwent a therapeutic plan in which different cognitive techniques were used to reduce the symptoms and modify the different distorted thoughts that he presented. Thanks to the immediate attention, it was possible to reduce the depressive states that the young man presented.